2016
DOI: 10.1007/s10571-016-0377-9
|View full text |Cite
|
Sign up to set email alerts
|

Increased Expression of 15-Hydroxyprostaglandin Dehydrogenase in Spinal Astrocytes During Disease Progression in a Model of Amyotrophic Lateral Sclerosis

Abstract: Amyotrophic lateral sclerosis (ALS) is an adult-onset, progressive, and fatal neurodegenerative disease caused by selective loss of motor neurons. Both ALS model mice and patients with sporadic ALS have increased levels of prostaglandin E2 (PGE2). Furthermore, the protein levels of microsomal PGE synthase-1 and cyclooxygenase-2, which catalyze PGE2 biosynthesis, are significantly increased in the spinal cord of ALS model mice. However, it is unclear whether PGE2 metabolism in the spinal cord is altered. In the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 25 publications
1
18
0
Order By: Relevance
“…PGE2 is known to be a potent proinflammatory mediator that is increased in postmortem brain tissue, cerebrospinal fluid, and serum from patients with sporadic ALS [6,29] and in both the cerebral cortex and spinal cord in the G93A mutant SOD1 transgenic mouse model of ALS [7,30]. A previous study from our laboratory showed that the PGE2induced cytotoxicity is mediated by activation of EP2 in differentiated NSC-34 cells [21].…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…PGE2 is known to be a potent proinflammatory mediator that is increased in postmortem brain tissue, cerebrospinal fluid, and serum from patients with sporadic ALS [6,29] and in both the cerebral cortex and spinal cord in the G93A mutant SOD1 transgenic mouse model of ALS [7,30]. A previous study from our laboratory showed that the PGE2induced cytotoxicity is mediated by activation of EP2 in differentiated NSC-34 cells [21].…”
Section: Discussionmentioning
confidence: 91%
“…Among them, PGE2 plays a pivotal role in the degeneration of motor neurons in humans and transgenic models of ALS. PGE2 is increased in cerebrospinal fluid from patients with sporadic ALS [6] and in the spinal cord of ALS model mice [7]. We have revealed that the level of microsomal PGE synthase-1 (mPGES-1), the enzyme catalyzing the final step of PGE2 biosynthesis, is significantly increased in motor neurons in the mouse model of ALS [8].…”
Section: Introductionmentioning
confidence: 99%
“…Mutations in NQO1 have been correlated with an increased risk of Alzheimer's disease (Bian, Zhao et al, 2008, Tsvetkov, Adamovich et al, 2011, while changes in PGDH expression have been linked to tumor growth in multiple cancers (Tai, Tong et al, 2007, Wolf, O'Kelly et al, 2006, as well as late-stage neurodegenerative disease (Miyagishi, Kosuge et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Immunohistochemistry. Immunohistochemistry was performed as described elsewhere [19,20]. Briefly, anaesthetised animals were perfused with 4% paraformaldehyde in phosphate-buffered saline (PBS).…”
Section: 5mentioning
confidence: 99%